Management and serious risk factors associated with unintentional injuries in paediatric emergencies in Spain - Eduardo J. Bardón Cancho; Cristina Arribas Sánchez; Arístides Rivas García; Jorge Lorente Romero; Paula Vázquez López; Rafael Marañón Pardillo (Elsevier, 2020)
Introduction: Thirty-eight million patients with injuries are treated in Emergency Departments every year, 90% of them being in the form of unintentional injuries (UIs). There are currently no global records of its management in Spain, or the risk factors that may be associated with them. The objective of this study is to describe the management of UIs in Spanish paediatric emergency departments, and to analyse factors related to the presence of serious injuries. Material and methods: A sub-study of a prospective multicentre observational study conducted over 12 months in 11 hospitals of the Spanish Paediatric Emergency Research Group (RiSEUP-SPERG), including children from 0 to 16 years of age consulting for UIs. Epidemiological data, circumstances of the injury, and data on emergency care and discharge destination were recorded on the 13th day of each month. Results: A total of 10,175 episodes were recorded, of which 1,941 were UIs 19.1%), including 1,673, of which 257 (15.4%) were severe. The most frequent complementary test was simple radiography (60.0%), and the most frequent procedure was limb immobilisation (38.6%). A significant relationship was found between presenting with a severe UI and age >5 years [OR 2.24 (95% CI: 1.61-3.16)], history of fracture [OR 2.05 (95% CI: 1.22-3.43)], or sports activity as a mechanism of injury [OR 1.76 (95% CI: 1.29-2.38)], among others. Conclusion: In Spain, most UIs are not serious. X-rays and immobilisation of extremities are the most frequently performed tests and procedures. Severe UIs were associated with individual factors, such as age >5 years or history of fracture, and with sports activity as a mechanism associated with severity. It is vital to implement measures to improve the prevention of these injuries and to support the training of caregivers through educational programmes. Resumen: Introducción: Cada año se tratan 38 millones de pacientes con lesiones en los servicios de Urgencias, siendo el 90% en forma de lesiones no intencionadas (LNI). Actualmente no existen registros globales de su manejo en España ni de los factores de riesgo que puedan llevar asociados. Nuestro objetivo es describir el manejo de las LNI en los servicios de Urgencias pediátricas (SUP) y analizar los factores relacionados con la presencia de lesiones graves. Material y métodos: subestudio de estudio observacional prospectivo multicéntrico desarrollado durante 12 meses, en 11 SUP de hospitales de la Red de Investigación de la Sociedad Española de Urgencias Pediátricas (RiSEUP-SPERG), incluyéndose niños de 0 a 16 años de edad que consultan por una LNI, los días 13 de cada mes. Se registraron datos epidemiológicos, circunstancias de la lesión y datos sobre la atención en Urgencias y destino al alta. Resultados: Se registraron 10.175 episodios, de los que 1.941 fueron LNI (19.1%), incluyéndose 1.673, de los cuales 257 (15.4%) fueron graves. La prueba complementaria realizada más frecuente fue la radiografía simple (60.0%) y el procedimiento más frecuente fue la inmovilización de extremidad (38.6%). Se encontró asociación significativa entre presentar una LNI grave y la edad >5 años [OR 2,24 (IC95% 1,61-3,16)], el antecedente de fractura [OR 2,05 (IC95% 1,22-3,43)] o la actividad deportiva como mecanismo lesional [OR 1,76 (IC 95% 1,29-2,38)], entre otros. Conclusión: En España, la mayoría de los casos de LNI no son graves. Las radiografías y la inmovilización de extremidades son las pruebas y procedimientos más frecuentemente realizados. La LNI grave se asoció con factores individuales, como la edad >5 años o el antecedente de fractura, y con la actividad deportiva como mecanismo asociado a gravedad. Resulta vital implementar medidas para mejorar la prevención de estas lesiones y apoyar la capacitación de los cuidadores mediante programas educacionales.